2015
DOI: 10.3390/rs70303020
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Boat Identification System for VIIRS Low Light Imaging Data

Abstract: Abstract:The ability for satellite sensors to detect lit fishing boats has been known since the 1970s. However, the use of the observations has been limited by the lack of an automatic algorithm for reporting the location and brightness of offshore lighting features arising from boats. An examination of lit fishing boat features in Visible Infrared Imaging Radiometer Suite (VIIRS) day/night band (DNB) data indicates that the features are essentially spikes. We have developed a set of algorithms for automatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 18 publications
0
124
0
3
Order By: Relevance
“…Each 16-line sweep across the Earth is termed a scan. A method was developed in 2014 to detect and filter out lightning (Elvidge et al 2015). The procedure involves calculating the relative radiance difference between adjacent lines of DNB data.…”
Section: Lightningmentioning
confidence: 99%
See 1 more Smart Citation
“…Each 16-line sweep across the Earth is termed a scan. A method was developed in 2014 to detect and filter out lightning (Elvidge et al 2015). The procedure involves calculating the relative radiance difference between adjacent lines of DNB data.…”
Section: Lightningmentioning
confidence: 99%
“…An initial filtering is done using thresholds placed on the DNB radiance and spike height index (SHI) (Elvidge et al 2015). SHI is calculated in two stages.…”
Section: Hep Detectionsmentioning
confidence: 99%
“…Nonetheless, some publications have shown that in particular fishing ships can be detected by their nightlights from space; e.g. Cho et al (1999) with OLS, and Elvidge et al (2015), Lebona et al (2016) and Straka et al (2015) with VIIRS.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the improved performance, VIIRS DNB data have been used in various applications, such as extracting urban areas [23][24][25][26][27], reflecting demographic and socioeconomic conditions [25,[28][29][30][31][32][33], monitoring nocturnal surface air quality [34][35][36], and so on [26,[37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%